Anomalous pressure dependence of the charge density wave and fermi surface reconstruction in BaFe2Al9 - Mohamed, Mahmoud; Sundaramoorthy, Muthukumaran; Jasim, Nabeel M.; Irshad, K. A.; Kuo, Chia Nung; Lue, Chin Shan; Carstens, Frederik; Bertrand, A.; Mito, M.; Klingeler, Rüdiger; Borisov, Vladislav; Delin, Anna; et al. (Physical review letters, 2025)
We investigate the pressure evolution of charge density wave (CDW) order in the intermetallic compound BaFe2⁢Al9, which undergoes a pronounced first-order CDW transition ∼1⁢1⁢2 K at ambient pressure. High-pressure electrical resistivity and magnetization measurements reveal a systematic enhancement of the CDW transition temperature (𝑇CDW) at a rate of ∼60 K/GPa, reaching 300 K under ∼3.2 GPa. The transition sharpness diminishes with pressure, indicating a crossover from first- to second-order behavior. Fermi liquid (FL) fits to the low-temperature resistivity reveal an increase in residual resistivity and a nonmonotonic evolution of the FL coefficient, indicating a pressure-induced Fermi surface (FS) reconstruction. Synchrotron x-ray diffraction reveals anisotropic lattice compression, a change in the compression trend of lattice parameters, and an abrupt change in microstrain at ∼3.6 GPa. Density functional theory calculations reveal pressure-induced flattening of quasi-two-dimensional FS sheets associated with the CDW nesting vector, consistent with enhanced nesting. These findings highlight the critical role of lattice strain and electronic structure evolution in stabilizing a high-temperature CDW phase, making BaFe2⁢Al9 a rare example of a three-dimensional material where pressure promotes rather than suppresses the CDW order.
Veröffentlicht: 2. Dezember 2025
Gesehen am 19.02.2026
Im Titel sind die Zahlen 2 und 9 tiefgestellt